Social Interaction and Stock Market Participation: A Study of Kathmandu Valley Investors - Shrestha, Sajeeb Kumar (NPRC Journal of Multidisciplinary Research, 2024)
This research aims to explore how social interaction influences stock market participation in the Kathmandu Valley. It utilizes a descriptive and causal study design, applying a positivist approach to investigate the phenomenon. The focus is on understanding the effects of social interactions on individuals' involvement in the stock market within this specific geographical context. A questionnaire survey was conducted to collect data about factors influencing participation in the stock market. A total of 399 samples were gathered from this population using convenience sampling. The data was then analyzed using several statistical techniques. Reliability analysis was employed to assess the internal consistency of the measurement instruments. The results of the analyses found that internet usage, social norms/community influence, and the influence of friends/partners had a significant impact on whether someone participates in the stock market. However, there was no evidence that parental involvement in the stock market influences their children's participation. In summary, the study examined how different factors relate to individuals' participation in the stock market through a survey and statistical analyses of the collected data. Internet access, social environment, and peer influences were found to affect participation, but not parental involvement.